Antibacterial therapy in the treatment of patients using dental implants in the limited alveolar bone volume conditions - A. M. Tsitsiashvili; A. M. Andrey Panin; A. V. Zabarovsky; D. V. Yunina; V. R. Gabidullina (LLC "Endo Press", 2020)
Prescribing antimicrobials to prevent and treat purulent-inflammatory complications during surgical interventions in outpatient practice is a common practice among dentists around the world. According to the National Center for Disease Control and Prevention (USA), approximately one in three antibiotic prescriptions is considered inappropriate. Due to the lack of scientific data, many clinicians are inclined to use antibiotics based on their experience or the experience of colleagues, which can lead to their unjustified prescription and the development of antibiotic resistance, which, according to the World Health Organization, is a growing international problem.